2014
DOI: 10.1186/s40497-014-0014-3
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of family capital & social capital on youth entrepreneurship – a study of Uttarakhand state, India

Abstract: The research paper intends to interpret how the three forms of family capital viz. family's financial capital, family's man power capital and family's human capital influences the career choice intention of students of HEI's of Uttarakhand, India. Additionally the study also evaluates the impact of student's individual social capital on his career intent. This is a quantitative study conducted at Uttarakhand state of India on a large sample of students studying in various professional courses of Uttarakhand. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 72 publications
4
26
0
4
Order By: Relevance
“…This is in line with other empirical research suggesting that social capital has an impact on entrepreneurial intentions of young people (Liñán and Santos, 2007;Sharma, 2014). Our findings also show that Croatian students were more familiar with the entrepreneurial environment.…”
Section: Resultssupporting
confidence: 82%
“…This is in line with other empirical research suggesting that social capital has an impact on entrepreneurial intentions of young people (Liñán and Santos, 2007;Sharma, 2014). Our findings also show that Croatian students were more familiar with the entrepreneurial environment.…”
Section: Resultssupporting
confidence: 82%
“…After publication it was highlighted by the author that the tables had been misplaced in the article Sharma (2014), the correct order is presented below: Table 1 should be placed below line the line that reads: "Based on the average annual income of their family, the students were divided into three different income categories. "…”
Section: Erratummentioning
confidence: 99%
“…Children of self-employed parents, however, are more likely to enter entrepreneurship, than children, which have parents from any other occupational group. Sharma (2014) on the other hand, claims that father's occupation of the respondents in their study was seen to have no influence on the career intention of students, which is in conflict with several of the earlier studies (Lindquist, Sol, and van Praag 2012;Carr and Sequeira 2007) and in line with the study in Turkey (Cetindamar et al 2012). There is a significant relationship with household income in childhood and startup (Schoon and Duckworth 2012;Jayawarna, Rouse, and Macpherson 2014).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 56%
“…The results are consistent with the findings of previous studies (Fairlie and Robb 2007;Carr and Sequiera 2007;Lindquist, Sol, and van Praag 2012), which emphasize the impact of family business on the entrepreneurial activity of young people. Sharma (2014) found that children of small entrepreneurs in India and Pakistan do not want to become entrepreneurs, and argue that young people are influenced more by external factors, especially the business environment, than by family. Given the relatively large proportion of female entrepreneurs of all age groups whose parents were farmers or skilled workers, the motive of Slovenian women entrepreneurs may also be highly related to the desire for a better income from working conditions from parents and to the family income, which is 254 management · volume 13…”
Section: Resultsmentioning
confidence: 99%